Development of a novel program for conversion from tetrahedral‐mesh‐based phantoms to DICOM dataset for radiation treatment planning: TET2DICOM. Issue 1 (11th October 2021) - Cheon, Bo‐Wi; Lee, Se Hyung; Han, Min Cheol; Min, Chul Hee; Han, Haegin; Kim, Chan Hyeong; Kim, Jin Sung
Abstract : Purpose: Tetrahedral mesh (TM)–based computational human phantoms have recently been developed for evaluation of exposure dose with the merit of precisely representing human anatomy and the changing posture freely. However, conversion of recently developed TM phantoms to the Digital Imaging and Communications in Medicine (DICOM) file format, which can be utilized in the clinic, has not been attempted. The aim of this study was to develop a technique, called TET2DICOM, to convert the TM phantoms to DICOM datasets for accurate treatment planning. Materials and methods: The TM phantoms were sampled in voxel form to generate the DICOM computed tomography images. The DICOM‐radiotherapy structure was defined based on the contour data. To evaluate TET2DICOM, the shape distortion of the TM phantoms during the conversion process was assessed, and the converted DICOM dataset was implemented in a commercial treatment planning system (TPS). Results: The volume difference between the TM phantoms and the converted DICOM dataset was evaluated as less than about 0.1% in each organ. Subsequently, the converted DICOM dataset was successfully implemented in MIM (MIM Software Inc., Cleveland, USA, version 6.5.6) and RayStation (RaySearch Laboratories, Stockholm, Sweden, version 5.0). Additionally, the various possibilities of clinical application of the program were confirmed using a deformed TM phantom in various postures. Conclusion: In conclusion, the TM phantom, currently the most advanced computational phantom, can be implemented in a commercial TPS and this technique can enable various TM‐based applications, such as evaluation of secondary cancer risk in radiotherapy.